'It looks like a breadbox': a pilot study investigating implementation of the Pepi-Pod® program with Aboriginal families in metropolitan South Australia. (10th June 2021) - Grant, Julian; Sivertsen, Nina; Deverix, Janiene; Steeb, Alice
Abstract: Aims: To collaboratively explore the cultural acceptance of the Pepi-Pod® program as an alternate safe sleep space and to explore the process of implementing the Pepi-Pod® program in a mainstream health service for Aboriginal families living in urban South Australia. Background: Aboriginal and Torres Strait Islander infants continue to die from sudden infant death syndrome (SIDS) and sudden unexpected death in infancy (SUDI) at rates three to four times greater than other infants born in Australia despite Council of Australian Governments commitment to halve the gap in the Indigenous infant mortality rate by 2018. The Pepi-Pod® program is evidenced in New Zealand and Queensland to provide a culturally appropriate safe sleep alternative that contributes to the reduction of SIDS and SUDI. We have no evidence of acceptability or feasibility when offered through mainstream services in metropolitan South Australia. Methods: With a focus on decolonizing the research process through a two-way process for mutual learning between Aboriginal and non-Aboriginal team members and community, a novel qualitative design was employed including photo elicited yarning sessions ( n = 7), focus groups ( n = 2), and field notes ( n = 15). Results: Four themes emerged: ' you don't have to worry' ; 'a way of sharing knowledge'; ' it looks like a bread box?' and 'need for consistent safe sleep messages'. The findings suggest that participants believe the Pepi-Pod® program may enrich Aboriginal families' lives evoking feelings of comfort and safety; however, the design could be improved to make them more culturally appropriate. There was confusion around safe sleep processes and education with a call for streamlining safe sleep messaging.